Concerns Regarding Article: 10.4103/ni.ni_800_22: Normative Data of Montreal Cognitive Assessment (MoCA) in Tamil Speaking Adults - A P Porrselvi (Neurology India, 2025)
Early engagement in research is fundamental to the advancement of gastroenterology as both a clinical and scientific discipline. Despite growing interest among trainees, many early-career gastroenterologists face substantial structural barriers: limited mentorship, insufficient methodological training, inadequate protected time, and competing clinical demands. This Special Communication presents a practical framework integrating an individual roadmap for research development with a society-led mentorship ecosystem. We outline strategies to cultivate a research mindset, develop foundational competencies, and generate meaningful academic impact-operationally defined across scholarly output, collaborative contribution, translational influence, and training pipeline dimensions. The role of professional societies in building structured mentorship pathways and collaborative networks is discussed with reference to the European Crohn's and Colitis Organization (ECCO) Y-ECCO and American Gastroenterological Association (AGA) FORWARD programmes. The evolving Saudi research landscape, including Vision 2030 priorities, Saudi Commission for Health Specialties (SCFHS) fellowship requirements, King Abdullah International Medical Research Center (KAIMRC), and King Abdulaziz City for Science and Technology (KACST) funding opportunities, is contextualized. Paired reflective accounts from a senior and an early-career gastroenterologist illustrate the practical realities of building a sustainable research career. Together, these perspectives and the accompanying operational framework provide a pragmatic, regionally anchored roadmap for nurturing the next generation of gastroenterology researchers.